GAMIFICATION IN ENGLISH LANGUAGE LEARNING: EFFECTS ON STUDENTS' ENGAGEMENT AND ACHIEVEMENT - Munawar Munawar; Mukhlisuddin Mukhlisuddin; Angela Mae Reyes (Sensei International Journal of Education and Linguistic, 2025)
Nowadays many teachers use games in learning English because the students easily get bored. This is called gamification, for example by giving points, badges, and leaderboards. This article discusses gamification in English language learning and its effect on students' engagement and achievement. The method used is literature review. The sources are taken from international journals and also national journals. The result shows that gamification can make the students more engaged in learning English, but for the achievement the result is not always the same because it depends on how the teacher uses it. Therefore the teachers should use gamification wisely and not only for fun.